Analyzing the Adoption of Online Shopping Using Extended Technology Acceptance Model: An Empirical Study on Five Districts of Nepal - Gaire, Bivek; Maharjan, Sanjeev (International Journal of Engineering and Management Research, 2023)
Recently, in Nepal, penetration of the internet has increased making every internet user a potential buyer of growing online shopping trend but the question arises of what motivates the consumer to buy online and how it has been adopted currently. This research aims to analyze the perception of Nepalese consumers toward online shopping with Extended Technology Acceptance Model (TAM2) as framework for examining various factors that influence shopping online. Responses of 460 participants were recorded for this study. A quantitative research approach was used and the collected data were analyzed by CB-SEM method using SPSS and AMOS. The research result shows that perceived ease of use has positive influence on perceived usefulness; perceived enjoyment and perceived cost have significant positive influence on attitude toward online shopping whereas perceived risk has negative influence on it. Moreover, behaviour intention to shop online is positively influenced by perceived usefulness, subjective norms, and attitude toward online shopping. This research supports that when consumers enjoy online shopping and find products at the right cost then they are motivated to shop online whereas risks associated with online shopping demotivate it. And, people’s behaviour to shop online is influenced by social influence, perceived usefulness, and attitude toward online shopping.